Paleontologia no Ensino Básico das escolas da Rede estadual do Rio de Janeiro: Uma avaliação Crítica - Duarte, Sarah Gonçalves; Arai, Mitsuru [UNESP]; Passos, Nádia Zélia Gomes; Wanderley, Maria Dolores (My University, 2016)
A problem exists in the teaching of basic concepts about Paleontology to students of the elementary schools in the Rio de Janeiro state network, because National Curricular Parameters (PCN) do not emphasize or value the role of Paleontology within the Natural Sciences. The purpose of the present work is to investigate the basic paleontological knowledge of these students by distributing a questionnaire comprising the following six questions: (1) Do you understand the meaning of the term Paleontology?; (2) Have you ever seen a fossil and, if so, where (magazine, movie, museum, other)?; (3) What is a fossil and are there any fossils in Brazil?; (4) What is a geologist?; (5) What is a dinosaur? (6) Have humans ever lived with dinosaurs? At present, five schools have been analyzed and 399 students tested. 16.6% answered that they understood what Paleontology is, but between them, 77.2% had only a superficial idea, 22.8% wrong ideas, and 83.4% had no idea whatsoever. 81.4% had already seen and understood what a fossil is, but 116 between them defined it incorrectly, 45.7% did not know how to define a fossil, 18.7% defined it incompletely or inadequately, and 18.6% indicated that they had never seen a fossil object nor had any idea about what a fossil is. 64.6% were aware of the existence of fossils in Brazil, 20.5% were unaware, and 14.9% failed to answer question 3. 38.6% answered that they knew something about the geological profession, only 9.1% could explain satisfactorily the work of a geologist, 73.4% explained it incorrectly or incompletely, 17.5% marked “yes”, but did not explain the performance of a geologist, and 61.4% stated that they did not know. 0.6% students defined reasonably well what a dinosaur is, 55.6% defined it incorrectly, 19% failed to answer question 5, and 24.8% gave an incomplete definition. 31.1% believed that humans lived with dinosaurs, 65.4% answered “no”, and 3.5% provided no answer. This study highlights deficiencies in the teaching of paleontology in the state school network.
Paleontology in elementary education of the state schools of the Rio de Janeiro: A critical evaluation
Keywords: Education; Paleontology; School